Rcf2 revealed in cryo-EM structures of hypoxic isoforms of mature mitochondrial III-IV supercomplexes - Hartley, Andrew M. (Proc Natl Acad Sci U S A, 2020)
The organization of the mitochondrial electron transport chain proteins into supercomplexes (SCs) is now undisputed; however, their assembly process, or the role of differential expression isoforms, remain to be determined. In Saccharomyces cerevisiae, cytochrome c oxidase (CIV) forms SCs of varying stoichiometry with cytochrome bc(1) (CIII). Recent studies have revealed, in normoxic growth conditions, an interface made exclusively by Cox5A, the only yeast respiratory protein that exists as one of two isoforms depending on oxygen levels. Here we present the cryo-EM structures of the III(2)-IV(1) and III(2)-IV(2) SCs containing the hypoxic isoform Cox5B solved at 3.4 and 2.8 Å, respectively. We show that the change of isoform does not affect SC formation or activity, and that SC stoichiometry is dictated by the level of CIII/CIV biosynthesis. Comparison of the CIV(5B)- and CIV(5A)-containing SC structures highlighted few differences, found mainly in the region of Cox5. Additional density was revealed in all SCs, independent of the CIV isoform, in a pocket formed by Cox1, Cox3, Cox12, and Cox13, away from the CIII–CIV interface. In the CIV(5B)-containing hypoxic SCs, this could be confidently assigned to the hypoxia-induced gene 1 (Hig1) type 2 protein Rcf2. With conserved residues in mammalian Hig1 proteins and Cox3/Cox12/Cox13 orthologs, we propose that Hig1 type 2 proteins are stoichiometric subunits of CIV, at least when within a III-IV SC.